Effect of Prophylactic Ondansetron on Spinal Anaesthesia-Induced Hypotension During Caesarean Section at Moi Teaching and Referral Hospital, Eldoret, Kenya - Omondi, Pauline A.; Shitsinzi, Rose; Itsura, Peter M.; Kirwa, Elisha K.; Mwangi, Henry R. (Kenya Medical Association, 2025)
Objective: To determine the effect of prophylactic ondansetron on the incidence of spinal anaesthesia- induced hypotension during caesarean section at Moi Teaching and Referral Hospital (MTRH), Kenya. Materials and Methods: A randomized, double-blind, control trial was conducted at MTRH involving 194 parturients at term gestation who underwent elective caesarean sections under spinal anaesthesia. Block randomization and consecutive sampling were employed. Participants were divided into two groups of 97: Group O received 4 mg intravenous ondansetron, and Group S received an equivalent volume of saline, both administered 15 minutes before spinal anaesthesia. Data on demographics, clinical, anaesthesia and surgical outcomes, vasopressor usage, and neonatal results were collected using a structured questionnaire and analyzed using STATA version 16. Statistical tests included the two proportions z-test, t-test, fisher’s exact and Mann-Whitney U test, with significance set at P < 0.05. Results: Both groups exhibited comparable baseline demographic and clinical characteristics. The mean age of participants was comparable between Group S (29.9 ± 4.8 years) and Group O (30.3 ± 4.7 years; P=0.56). A majority in both groups were under 35 years of age (Group S: 80.4%, Group O: 77.3%), with no statistically significant difference (P=0.598). The incidence proportion of spinal anaesthesia- induced hypotension (SAIH) was 85.6%. Group O had lower SAIH occurrence (77.3%, n=75) compared to group S (93.8%, n=91), P=0.001. Mean systolic blood. pressure variations across time intervals did not differ significantly between Group S and Group O (P>0.05). Conclusion: Prophylactic 4mg intravenous ondansetron is effective in reducing the incidence of SAIH.
Keywords: prophylactic ondansetron; spinal anaesthesia; Kenya